Gene Polymorphisms of TNF-238G/A, TNF-308G/A, IL10-1082G/A, TNFAIP3, and Comorbidity Occurrence: A Comprehensive Review - Azhar Ahmed Abualr et al. (International Journal of Scientific Research and Innovative Studies, 2024)
Gene polymorphisms play a pivotal role in susceptibility to various diseases, including inflammatory and autoimmune disorders. Tumor Necrosis Factor-alpha (TNF-α) gene polymorphisms (-238G/A and -308G/A), interleukin-10 (IL-10) gene polymorphism (-1082G/A), and TNFAIP3 (TNF-α-induced protein 3) polymorphisms are associated with inflammatory pathways and immune responses. These genetic variations are implicated in the occurrence and severity of comorbidities such as cardiovascular diseases, metabolic syndrome, autoimmune disorders, and infections. This review highlights the association of these polymorphisms with comorbid disease development, providing an analysis of the genetic contributions to disease pathophysiology and clinical implications. Received Date: November 05, 2024 Accepted Date: November 26, 2024 Published Date: December 01, 2024 Available Online at https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/284 https://doi.org/10.5281/zenodo.14510785